PENINGKATAN EFIKASI DIRI MASYARAKAT DALAM PENCEGAHAN TUBERKULOSIS BERBASIS BUDAYA - Sulistyono, R Endro; Sukartini, Tintin; Makhfudli, Makhfudli; Nursalam, Nursalam; Rr Soenarnatalina M, Rr Soenarnatalina M; Hidayati, Laily (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2017)
Numbers of TB in Indonesia are increasing by years. One of the causes of TB control challenges is the lack of community awareness of TB disease. The Madurese are very culturally and very obedient to the kiai (religious leaders) as well as the level of TB disease in areas where they are still high. This study aimed to explore the community's self-efficacy towards TB prevention through a cultural approach. Method: This study is a quasi experimental study with two control and treatment groups (pre-post design). The sample of this study were 100 respondents (50 controls groups and 50 treatment groups) which selected by simple random sampling based on the inclusion criteria. Data then analyzed by using paired t test dan independent t test. Result: there was significant effect of P value = 0.000 in treatment group, there was self efficacy improvement after the delivery of intervention with culture approach. Discussion: Interventions for TB prevention require innovation with cultural approaches adopted by the community (such as working with kiai, people who are considered to have charisma for certain community groups) to make it easier to implement TB prevention. Keywords : Tuberculosis, culture, efficacy